‘When I get upset about my children’s problem, I can’t concentrate’- International students reflect on their roles as parents while studying in the UK - Pinter, Annamaria (International Journal about Parents in Education, 2023)
This article explores international student–parents’reflections about their children’s difficulties as temporary sojourners in UK schools, and the ways in which they attempt to support them in the process of settling down at school. The data is drawn from qualitative research interviews (Richards 2003; Hiller & DiLuzio 2004) with 25 student parents. The emerging themes focus on parents’ attempts to assist their children with academic and linguistic problems and with making and maintaining friendships. A major theme emerges about the role of host schools, and also about the parents’ emotional burden regarding their own compromised situation. The data reflects overall that the first year of sojourn is often more problematic than expected, and thus more research in this area is needed to address how universities interested in internationalisation can best support these student parents. Further, more research is needed into ways in which local schools, including both teachers and learners can best accommodate international children focussing on their unique competencies.